ANALISIS MODEL PENERIMAAN TEKANALISIS MODEL PENERIMAAN TEKNOLOGI PROPERTI MANAGEMENT SYSTEM TERHADAP KINERJA MANAJEMEN PADA ERA REVOLUSI INDUSTRI 4.0NOLOGI PROPERTI MANAGEMENT SYSTEM TERHADAP KINERJA KEUANGAN PADA ERA REVOLUSI INDUSTRI 4.0 - Utomo, Budi; Prianthara, I.B. Teddy (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
ABSTRACT   The purpose of this research is to analyze the influence of the working culture on the belief in the system and personal innovation, to analyze the influence of confidence in the system and personal innovation to the perception of usability and perception of ease, to analyze the influence of usability perception, the perception of ease and the working culture of financial performance. The population in this study is the entire employee of Archipelago International Indonesia Area Bali with 56 employees. Sampling using the saturated sample method. Data analysis in this study uses PLS (Partial Least Square) 3.0 . The results of the analysis show that the working culture has a positive and significant impact on confidence in the system and personal innovation. Confidence in the system and personal innovation have a positive and significant effect on the perception of usability and perception of ease. Perception of usability and perception of ease of influence is positive and significant to financial performance. While the working culture has no significant effect on financial performance.   Keywords: work culture, system confidence, personal innovation, financial performance